Volume 2: 32nd Computers and Information in Engineering Conference, Parts a and B 2012
DOI: 10.1115/detc2012-71133
|View full text |Cite
|
Sign up to set email alerts
|

Web-Enabled Real-Time Quality Feedback for Factory Systems Using MTConnect

Abstract: Quality is a key element to success for any manufacturer, and the fundamental prerequisite for quality is measurement. In the discrete parts industry, quality is attained through inspection of parts but typically there is a long latency between machining, quality measurement and part/process assessment. Since manufacturing systems are by their nature imperfect, it is imperative to indentify and rectify out-of-tolerance processes as soon as possible. Rapid quality feedback into the factory operation is not a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Edrington et al [29] proposed a web-based machine monitoring system that provides data collection, analysis, and machine event notification for MTConnect compatible machines. MTConnect-based system monitoring is also used for retrieving in-process parts data to quickly generate machining quality reports [30]. Previous research also demonstrated a much wider application of MTConnect towards smart manufacturing, such as sustainable machining [31], machining simulation [32], cloud manufacturing [33], intelligent maintenance [34], and cyber-physical machine tools [35].…”
Section: • Mtconnectmentioning
confidence: 99%
“…Edrington et al [29] proposed a web-based machine monitoring system that provides data collection, analysis, and machine event notification for MTConnect compatible machines. MTConnect-based system monitoring is also used for retrieving in-process parts data to quickly generate machining quality reports [30]. Previous research also demonstrated a much wider application of MTConnect towards smart manufacturing, such as sustainable machining [31], machining simulation [32], cloud manufacturing [33], intelligent maintenance [34], and cyber-physical machine tools [35].…”
Section: • Mtconnectmentioning
confidence: 99%
“…• Probabilistic, physics-based process-property models to predict and guarantee that a manufactured product's range of performance lies within design requirements • A rapid qualification schema that employs statistical methods and probabilistic simulation tools for low-cost, high-confidence prediction of system performance • New manufacturing and fabrication processes that result in improved performance, reduced production times, and more affordable manufacturing • Military-service-affiliated manufacturing demonstration facilities that serve as repositories of focused manufacturing knowledge and infrastructure The Accelerated, Adaptive Army Fabrication is a new ManTech-funded project whose output will be a prototype weapon system employing Army-owned design and manufacturing knowledge for next-generation improvement and sustainment. Accomplishments so far include development of software tools to handle requests for quotes, deployment of an MTConnect enabled [13] platform for inspection data, testing and validation of additive manufacturing equipment, and piloting of machining optimization tools.…”
Section: Mick Maher Defense Advanced Research Projects Agency (Darpa)mentioning
confidence: 99%